Simplified above-knee amputation with short operation time and minimal blood loss for ultra-high-risk patients under nerve block and local anesthesia - Marin Mimura, MD; Yu Kagaya, MD, PhD; Hikaru Kono, MD; Toshiki Furukawa, MD; Tetsu Kojima, MD; Fumio Onishi, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
Background: Above-knee amputation (AKA) is not suitable for certain ultra-high-risk patients owing to its surgical invasiveness and accompanying anesthesia. We developed a simple technique for AKA under nerve block and local anesthesia, which is quick and associated with little blood loss compared with conventional AKA. We report our experience with this procedure. Methods: The affected extremity was provided analgesia with a combination of nerve block (femoral and sciatic nerve block) and local anesthesia of a low concentration. Our amputation method comprises two key stages: an initial knee disarticulation and a subsequent supracondylar osteotomy. The muscles were cut at the tendon, the artery was ligated at the popliteal fossa, and subperiosteal dissection for amputation of the femoral condyle was minimized. The wound was closed roughly without osteomyodesis. We included 12 consecutive patients on whom the procedure was performed (7 with chronic limb-threatening ischemia and 5 with acute limb ischemia) while they were taking anticoagulant or antiplatelet drugs. All the patients had an American Society of Anesthesiologists physical status of class III or higher (class III: severe systemic disease with substantive functional limitations [n = 6]; class IV: severe systemic disease that is a constant threat to life [n = 6]). Results: All the surgeries were successfully completed. The mean ± standard deviation operation time was 36.0 ± 8.4 minutes, and blood loss was 52.1 ± 37.5 mL. Minor perioperative wound complications occurred in only two cases. The patients' activities of daily living after the operation were the same as before surgery in each case. Conclusions: The presented method is a potential treatment for severe lower limb necrosis in ultra-high-risk patients for whom traditional AKA is impossible owing to intolerance for general anesthesia and invasive surgery. However, the long-term results are as yet unknown.